A prospective randomized controlled trial comparing the effects of dexmedetomidine and fentanyl on attenuation of pressor response during laryngoscopy and intubation in neurosurgical patients - Anjum, Shazia; Chhiber, Sarbjit Singh; Khan, Majid; Ali, Zulfiqar; Khan, Talib (International Journal of Research in Medical Sciences, 2019)
Background: Laryngoscopy is associated with a sympathetic response that results in a rapid increase in blood pressure and heart rate in these patients. The mechanisms underlying these hemodynamic changes are incompletely understood. They may be caused by a reflex sympathetic discharge due to stimulation of the upper respiratory tract. It has been observed that hemodynamic responses to tracheal intubation are associated with an increase in plasma catecholamine concentrations and are attenuated by β-adrenergic blockade. These hemodynamic changes may be undesirable particularly in neurosurgical patients. Aim of the study is the present study was prospective, randomized, double-blind conducted to evaluate the efficacy of dexmdetomidine and fentanyl in attenuation of pressor responses to laryngoscopy and intubation in neurosurgical patients undergoing lumbar spine surgeries. Methods: A total of 60 patients of 18–65 years, American Society of Anaesthesiologists Class I/II of undergoing elective neurosurgical procedures were included in the study. The patients were divided into two groups of 30 patients each. Group D received dexmedetomidine and Group F received Fentanyl. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial blood pressure (MAP) were recorded preoperatively (baseline), at 5 and 8 minutes after infusion of study drug, before induction, 1 minute after induction, 2 minute after intubation, 5 minute after intubation, 10 minute after intubation and 15 minute after intubation. Results: There was a better control of Heart rate, systolic blood pressure, diastolic blood pressure and mean arterial pressure in Group D when compared to Group F during laryngoscopy and after intubation. Conclusions: The present study shows that dexmedetomidine suppresses hemodynamic responses effectively than fentanyl.